Nilai nilai yang terkandung dalam kesenian bantengan - maulana, raditya alvin (Maliki Interdisciplinary Journal, 2025)
Indonesia, a country rich in natural and cultural potential, features a variety of regional art forms, one of which is a traditional performing art known as bantengan. This research paper explores the cultural meanings and values contained in bantengan, a folk art that originated in rural communities and reflects their unique regional identity. Bantengan combines elements of drama, martial arts, music, dance and mystical rituals, often reinforced by trance experiences during performances. This research uses a qualitative literature review methodology, which systematically analyzes various sources to uncover the positive and negative impacts of bantengan on community dynamics. The focus of the research includes social cohesion, opportunities for informal economic activities, and efforts to preserve cultural heritage. The findings show that while bantengan is able to instill values of courage, solidarity, spirituality, and respect for nature, the art also faces challenges, such as negative behavior among participants. Thus, this study emphasizes the importance of preserving traditional arts such as bantengan. This is not only related to its entertainment value, but also to its role in instilling moral lessons and maintaining cultural identity for future generations.